ANALISIS PENGELOLAAN PENGADUAN PELANGGAN DI JARINGAN INDIHOME - Agustin Amborowati (Fakultas Ekonomi Universitas Islam 45, 2024)
One of the internet providers is PT Telekomunikasi Indonesia, Tbk with its product IndiHome. This study aims to analyze the implementation of complaint management on IndiHome network disruptions by PT Telkom Akses Solo. The research design used by the author is a case study with a descriptive method. The object of this study is located on Surakarta. Then the author used research data from interviews and observations regarding the management of complaints of IndiHome customer network disruptions. In addition, mendescripting problems and solutions to problems experienced by PT Telkom Akses Solo when managing complaints of customer network disruptions. Through this study, the author obtained results regarding the implementation of customer complaint management on the IndiHome network by PT Telkom Akses Solo. Based on the results of the study, the treatment provided is quite good and in accordance with the established procedures.